2010
DOI: 10.1002/adem.201000234
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Graphite Crystal Structure and Growth Mechanisms Using FIB and 3D Image Analysis

Abstract: Considering the significant influence of the morphology of graphite inclusions on the properties of cast iron it is important to understand the correlation between manufacturing parameters and resulting microstructure. In particular, understanding the effect of alloying elements and inoculants on the formation and growth mechanisms of the graphite particles provides the basis for exact tailoring of the microstructure and thus exact tailoring of effective properties of cast iron. Experimental observations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This is probably because that the triangular Cu(111) plane is prone to have more similarities in crystallographic geometry as the hexagonal graphene lattice than other crystal planes, thus reducing the nucleation barrier, since the lattice mismatch between graphene and underlying metal will cause an additional energy cost (E is increased). 29,32 This result is also supported by the previous report that the additional energy cost due to the lattice mismatch can result in the destabilization of graphene nuclei. 29 Although there has been some concern that graphene may preferentially nucleate and grow on specific Cu crystallographic surfaces, 33 our results provide the first CVD-derived experimental evidence.…”
Section: Discussion On Influencing Factors Of Graphitization Of Amorpsupporting
confidence: 84%
“…This is probably because that the triangular Cu(111) plane is prone to have more similarities in crystallographic geometry as the hexagonal graphene lattice than other crystal planes, thus reducing the nucleation barrier, since the lattice mismatch between graphene and underlying metal will cause an additional energy cost (E is increased). 29,32 This result is also supported by the previous report that the additional energy cost due to the lattice mismatch can result in the destabilization of graphene nuclei. 29 Although there has been some concern that graphene may preferentially nucleate and grow on specific Cu crystallographic surfaces, 33 our results provide the first CVD-derived experimental evidence.…”
Section: Discussion On Influencing Factors Of Graphitization Of Amorpsupporting
confidence: 84%
“…[1][2][3][4][5][6][7][8] Considering that nodularizing treatment is a series of processes involving the dissolution/melting of nodularizing agent, followed by reactions with solutes (S, O etc.) to form inclusions and,…”
Section: )mentioning
confidence: 99%
“…In investigating the formation mechanism of nodular graphite, numerous studies have since identified the presence of these inclusions at the center of nodular graphite. [6][7][8] Hence, it is ascertained that non-metallic inclusions of REEs could serve as effective heterogeneous sites for graphite nucleation. In studying the effects of non-metallic compounds on the nucleation of graphite in cast iron, Ueda et al experimentally determined that compounds with low interfacial energy with the nucleated solids showed a stronger nucleating efficiency and, the interfacial energy between two solids were affected by crystallographic mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…This anisotropy is related to graphite's layered structure with strong covalent bonds within the basal planes and weak van der Waals bonds between them, which makes graphite a transversely isotropic material (Figure 1.c) [2,5,[45][46][47][48][49]. This anisotropy is related to graphite's layered structure with strong covalent bonds within the basal planes and weak van der Waals bonds between them, which makes graphite a transversely isotropic material (Figure 1.c) [2,5,[45][46][47][48][49].…”
Section: Graphitementioning
confidence: 99%
“…This leads to particles in which some parts resemble the graphite crystalline structure of nodular graphite, while in other parts it resembles the crystalline structure of lamellar graphite [2,45,46,49]. This leads to particles in which some parts resemble the graphite crystalline structure of nodular graphite, while in other parts it resembles the crystalline structure of lamellar graphite [2,45,46,49].…”
Section: Graphitementioning
confidence: 99%